A Questionnaire Based Study on Practice of Visits Related to Post-Operative Anesthesia - Tooba Mughal, Zara Rizwan, Nasir Ali Rahim Najjad, Salman Mohsin (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To assess the frequency of anesthesiologists practicing post-op anesthesia visit and to determine the reasons of not regularly performing post-operative anesthesia visit. Study design: Cross-sectional study. Place and duration of study: Tertiary and Secondary care hospitals of Karachi from 7th November 2019 to 7th April 2020. Methodology: One hundred and eighty four anesthesiologists were enrolled. The eligibility of the anesthesiologist was assessed based on the eligibility criteria. The PI or the study team member was met the anesthesiologist on the decided date and time and asked him/her to complete the questionnaire. The questionnaire would take 10-15 minutes. This questionnaire was used to assess post-op practice and reasons for not performing post-operative anesthesia visit. Results: The average age of the participants was 30.94±2.98 years. 52.72% of the anesthesiologists do not practice PAVs and 47.28% reported that they perform PAVs. Furthermore, majority of the anesthesiologist who do not practice PAVs reported that lack of time the most common reason for not performing PAVs regularly (80.4%) followed by long distances to the patients to be covered (19.6%), patients already discharge (18.6%) extensive research (17.5%) and others (13.4%). Conclusion: Most of the anesthesiologists do not practice PAVs. Considering the high appreciation of post-anesthesia visits by anesthesiologists, as well as the relevant incidence of postoperative complications detected during these visits, it seems desirable to consider organizational improvements for post-anesthesia care. Keywords: Post-operative anesthesia visit, Surgeon satisfaction, Post-operative complications of anesthesia